Analysis Of The Effectiveness Strategy Of E-Samsat In Increasing Motor Vehicle Tax Revenue At The Kisaran Pependa UPTD - Kiki Ardiani; Muhammad Lathief Ilhamy Nasution; Kusmilawaty (LP2M IAIN Palopo, 2025)
This research was conducted at the Kisaran Regional Revenue Service Office (UPTD Pependa) to analyze the effectiveness of e-Samsat in increasing motor vehicle tax revenue, addressing the issue of low public participation in paying taxes through the e-Samsat application. The method used in this study was a qualitative research method with a descriptive approach. Data collection techniques used were field studies consisting of observation, interviews, and documentation. The findings indicate that E-Samsat is very efficient in improving internal administrative processes, reducing recording errors, and accelerating financial reporting. However, its effectiveness in increasing overall PKB revenue remains low, marked by minimal taxpayer participation (0.153%). This is due to uneven and ineffective socialization, as well as slow community adaptation due to low digital literacy, limited access to technology, and doubts about the security of online systems amidst rampant fraud and lack of education. The implication is that although E-Samsat is an efficient innovation, its full potential in increasing PKB revenue has not been achieved, requiring a more comprehensive and equitable socialization strategy, increased technological accessibility, and ongoing education to build public trust and digital literacy.